2007
DOI: 10.1111/j.1574-695x.2007.00255.x
|View full text |Cite
|
Sign up to set email alerts
|

Mice protected by oral immunization withLactobacillus reuterisecreting fusion protein ofEscherichia colienterotoxin subunit protein

Abstract: A green fluorescent protein (gfp) gene was ligated to the Lactobacillus reuterispecific nisin-inducible expression-secretion vector pNIES, generating a pNIES-GFP vector capable of secreting the cloned gene as a GFP-fusion protein with fluorescent activity. To develop this system as a live vehicle carrying the heat-stable enterotoxin (ST) and heat-labile enterotoxin B (LT B ) of the enterotoxigenic Escherichia coli (ETEC), a recombinant 5 0 -ST-LT B -3 0 DNA fragment was cloned into pNIES-GFP. The resulting L. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
35
0

Year Published

2008
2008
2023
2023

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 48 publications
(37 citation statements)
references
References 34 publications
2
35
0
Order By: Relevance
“…Recent studies have shown that oral administration of a number of lactobacilli expressing recombinant immunogens induces local mucosal (42) and systemic antibody responses (62). Other studies have explored this further and showed that immune responses induced via lactobacilli delivered through oral vaccination confer some protection against challenge with the respective pathogen (27,31,32,60). Because of its GRAS status, a live vaccine based on Lactobacillus will be more readily acceptable to the public than an oral vaccine based on a wellrecognized pathogen.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Recent studies have shown that oral administration of a number of lactobacilli expressing recombinant immunogens induces local mucosal (42) and systemic antibody responses (62). Other studies have explored this further and showed that immune responses induced via lactobacilli delivered through oral vaccination confer some protection against challenge with the respective pathogen (27,31,32,60). Because of its GRAS status, a live vaccine based on Lactobacillus will be more readily acceptable to the public than an oral vaccine based on a wellrecognized pathogen.…”
Section: Discussionmentioning
confidence: 99%
“…There is evidence that some strains of lactic acid bacteria have a favorable influence on physiologic and pathological processes of the host due to their specific health-promoting probiotic characteristics that relate to modulation of the immune system (15,36,41). Some strains of lactic acid bacteria polarize the naïve immune system by skewing it toward Th1 responses (41, 56).There have been a number of reports of oral vaccine candidates established from genetically modified pathogenic bacteria, such as Salmonella and Listeria species (1, 2, 30, 45, 52), or commensal bacteria, such as Lactococcus lactis and Lactobacillus species (27,31,32,60). The latter are food-grade bacteria that have GRAS status (generally regarded as safe).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…The first carrier to which ST was genetically fused was the A subunit of the heat-labile enterotoxin (LT-A), and the LT-A-ST fusion protein was shown to react with an ST monoclonal antibody (41). In later studies, ST has been fused to a number of different carriers in various ways, including LT-B (4, 9, 14), pLT(Arg192Gly) (73), CT-B (39, 40), the outer membrane protein OmpC (38), the ZZ moiety derived from Staphylococcus aureus protein A (28), the major subunit ClpG of Escherichia coli CS31A fimbriae (2), Salmonella flagellin (35), and green fluorescent protein (GFP) (65). The most successful genetic fusions of ST to suitable carriers, from a human vaccine perspective, are summarized in Table 1.…”
Section: St Vaccinologymentioning
confidence: 99%
“…An oral vaccine is also desirable, because it can be administrated easily to children without the need for injections. Attempts at expressing ST in attenuated bacteria intended for oral delivery include use of attenuated Salmonella, Shigella, and Lactobacillus reuteri (4,65,74). Alternative routes to elicit mucosal responses could include transgenic foods or nasal or rectal administration.…”
Section: St Vaccinologymentioning
confidence: 99%